Gambaran Kepatuhan Pengobatan Pasien Diabetes di Puskesmas Kedurus Pada Era Pandemi Covid-19: Overview of Diabetes Patient Medication Adherence at the Kedurus Health Center in the Covid-19 Pandemic Era - Wishesa, Clara Cahyaning; Kamil, Adnan Shaubilhaq Insan (Tadulako University, 2023)
Diabetes is a chronic disease characterized by chronic blood glucose levels that exceed normal threshold. High blood glucose levels occur because the pancreas does not produce enough insulin or when the body is unable to use the insulin it produces effectively. Optimal diabetes management should not be interrupted and must be carried out continuously by the patient, but with Covid-19 pandemic, patient access to treatment is limited. This study aims to describe the level of compliance of diabetic patients in carrying out their treatment at the Kedurus Health Center during the Covid-19 pandemic and to determine the relationship between patient characteristics and medication adherence with diabetes treatment. This study is an observational study with a cross sectional approach conducted at the Kedurus Health Center in July-October 2021. The sample of this study were diabetic patients at the Kedurus Health Center with inclusion criteria aged 26-75 years and lived in the working area of ​​the Kedurus Health Center. The data used in this study is secondary data obtained from the patient's medical records available at the Kedurus Health Center. The results of this study found that more than half of the respondents have poor medication adherence (54.3%) during Covid-19 pandemic era. There was no significant relationship between gender (p=0,370), age (p=0,562), distance from home to health facilities (p=0,683), and the type of oral antidiabetic drug consumed (p=0,072) with medication adherence of the diabetes patients at the Kedurus Health Center during the Covid-19 pandemic era.